Training on Making Liquid Organic Fertilizer (POC) from Stale Rice in Silaberanti Village, Jakabaring District, Palembang City - Amir, Nurbaiti; Paridawati, Ika; Syafrullah, Syafrullah; Afriyatna, Sisvaberti; Rosianty, Yuli (Universitas Muhammadiyah Palembang, 2021)
Organic fertilizer is the final result of the decomposition of parts or remains of plants and or animals that have undergone engineering, in solid or liquid form. Household waste, one of which is stale rice, is usually thrown away directly into the environment, even though it can still be used, for example, made as liquid organic fertilizer. For this reason, it is necessary to remodel household waste, especially stale rice, into liquid organic fertilizer by utilizing existing local microorganisms. This Community Service aims to provide motivation and knowledge and skills to the community on how to make liquid organic fertilizer from stale rice by utilizing local microorganisms. The location of Community Service was held at RT.28 RW.007 Silaberanti Village, Jakabaring District, Palembang City, on January 30, 2021. The method used was counseling and training to participants on the manufacture of liquid organic fertilizer (POC) from stale rice. The implementation of the activity was attended by 12 participants, who were followed with enthusiasm and discussions and questions and answers during the training. The results of this Community Service show that the service method in the form of counseling, training and question and answer is very appropriate in motivating the community to be able to make liquid organic fertilizer from stale rice.